Incidental radiological finding of charm needles in the hip region: A potential surgical precaution. - Rampal , Sanjiv; Hassan, Ya Mohamad; Sikkandar, Mohamed Faizal (GESDAV, 2012)
We report an unusual incidental radiographic finding of this 71 year old Malay lady who suffered a closed neck of femur fracture due a fall at home which had undergone total hip replacement at our establishment .This is one of the only papers showing incidental occurrence of susuk or charm needles in hip region in orthopaedic field.